Investigating the Effectiveness of Problem-Focused Couple Therapy and Metacognitive Therapy Approach on Strengthening Communication Skills and Reducing Marital Conflicts - Sadat Banihashem, Kobra; Sadeghi, Zeinab; Gorji Chalespari, Fatemeh; Mivehvar , Negar; Hoseini, Seyedeh Sara (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aims to analyze how problem-focused couple therapy and metacognitive therapy can enhance communication skills and decrease marital conflicts. Methodology: The study utilized a semi-experimental design, consisting of a pre-test, post-test, and a three-month follow-up period, with two groups receiving interventions and one serving as the control group. The participants were couples seeking family counseling and dealing with marital conflicts in Shiraz between July and October 2023. A total of 42 couples were selected for the study using purposive sampling. One group received metacognitive training consisting of seven 60-minute sessions twice a week, while the other group received problem-focused couple therapy with six 60-minute sessions twice a week. The research utilized the Communication Skills Test-Revised (CSTR) and Marital Conflict Questionnaire-Revised (MCQ-R) as assessment tools. The statistical analysis in this study utilized the Kruskal-Wallis H test, repeated measure ANOVA, and Bonferroni post hoc test in SPSS version 27, with a p-value set at 0.05. Findings: The most recent study’s results show that the P-value for the Between-Subjects Effects related to the Marital Conflict variable was deemed statistically significant (p<0.001). Likewise, the interaction effects between groups and time in the Within Subjects Effects also showed significance for the Marital Conflict variable (P=0.021). Additionally, the P-value for the Between-Subjects Effects was significant for the components of the Ability to receive and send messages, Emotional regulation, and Insights into the communication process (p<0.01). The analysis of the Between-Subjects Effects also revealed significant P-values for listening skills and Assertiveness components (p<0.01). Conclusion: This research shows that problem-focused couple therapy and metacognitive therapy help improve communication skills and reduce marital conflicts. These findings can assist couples looking to enhance their relationships and promote empathy and mutual understanding in selecting the most suitable treatment to address their issues.